STRATEGI PEMASARAN BOKAR PADA SISTEM LELANG APKARKUSI DI DESA GUNUNG KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Kusumawaty, Yeni; Eliza, Eliza; Pangestra, Gusti (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2023)
Apkarkusi is an institution formed by the Government of Kuantan Singingi Regency as a Government action to address the problem of low rubberprices and not the optimal quality of bokar. Research objectives: 1) To find out the characteristics of rubber planters who are members of Apkarkusi in Gunung Village, 2) To know the marketing strategy used by Apkarkusi in Kuantan Singingi Regency. Sampling was purposive sampling withthe criteria of farmers joining Apkarkusi and one Apkarkusi administrator, using 41 respondents from 3 farmer groups and the Head of the Apkarkusi auction market division. Data analysis used descriptive qualitative analysis and SWOT analysis. The results of the study were 51-60 years old (34.15%), land area <2 ha (65.85%), last education was junior high school (36.59%), experience in farming (46.34%), number of family dependents 3–5 souls (63.42%). Recommend a ranking order strategy: 1) Implementing the 4S concept and maintaining the quality of bokar to obtain a high and stable selling price to minimize rubber planters changing land functions. 2) Maintaining the quality standards set by Apkarkusi to maintain buyer trust. 3) Applying the 4S concept and having regular buyers can increase the selling price of bokar. The findings of this study can have an impact on long-term development goals (SDG’s), such as creating a marketing plan based on the 4S idea, maintaining bokar quality, and engaging customers while dramatically increasing bokar selling prices. This directly affects the revenue of rubber growers, the majority of whom are in vulnerable economic groups